COSTS AND REVENUE OF IRRIGED AND RAINFED RICE FARMING IN KLATEN DISTRICT - Bimoseno Sepfrian; Rahmawati Setiyani; Dian Septi Purwani (LPPM Universitas Duta Bangsa Surakarta, 2022)
Population growth and continuous economic growth increase the demand for food, water and energy. Food security is a condition where food needs are met both for households, such as quality, safety, nutrition, equitable distribution, and affordable. Food security is an important thing in food self-sufficiency. The purpose of this study was to analyze the cost of income and efficiency in irrigated and rainfed rice fields in Klaten district. The method used in determining the sample is done by purposive sampling. Data analysis uses farming analysis such as cost, income and efficiency analysis. The results show that rainfed and irrigated rice fields in Klaten Regency are profitable and efficient in terms of efficiency. The income from irrigation rice farming obtained by farmers is 22,344,090.67/ha and Rainfed is 15,037,684.32/ha and the efficiency of Irrigated lowland rice farming is Rp. 2.11 and Rainfed is Rp. 1.46.